2016
DOI: 10.1093/humrep/dew321
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seminal impairment in HIV-infected men under antiretroviral therapy

Abstract: No external funding was used for this study. The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Pilatz et al [17] compared semen parameters in a smaller sample of 116 HIV-1 positive patients under HAART to the WHO reference values and found that, in each category of semen parameters, about 25% of patients had semen parameters below the fifth percentile of WHO reference values, in line with our results. More recently, a prospective study conducted on 139 HIV-infected men showed median values of semen parameters within the normal WHO range, but up to 19% of HIV-positive males under stable therapy showed at least one parameter of semen quality below the normal range [18]. Morever, this study showed no associations between HAART duration and semen quality, in line with our findings [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pilatz et al [17] compared semen parameters in a smaller sample of 116 HIV-1 positive patients under HAART to the WHO reference values and found that, in each category of semen parameters, about 25% of patients had semen parameters below the fifth percentile of WHO reference values, in line with our results. More recently, a prospective study conducted on 139 HIV-infected men showed median values of semen parameters within the normal WHO range, but up to 19% of HIV-positive males under stable therapy showed at least one parameter of semen quality below the normal range [18]. Morever, this study showed no associations between HAART duration and semen quality, in line with our findings [18].…”
Section: Discussionsupporting
confidence: 90%
“…More recently, a prospective study conducted on 139 HIV-infected men showed median values of semen parameters within the normal WHO range, but up to 19% of HIV-positive males under stable therapy showed at least one parameter of semen quality below the normal range [18]. Morever, this study showed no associations between HAART duration and semen quality, in line with our findings [18]. Conversely, a significant association between exposure to EFV and the presence of sperm dysmotility was identified by Frapsauce et al [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ROS may affect the fluidity of the plasma membrane of the sperm cell resulting in germ cell apoptosis, thereby affecting the sperm count (Aitken & Fisher, ; Agarwal et al ., ). Although our study never assessed the effects of the individual component of HAART, Efavirenz has been reported to negatively affect sperm motility (Frapsauce et al ., ; Jerónimo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Growing evidence has shown that HAART has deleterious effects on the testes and the overall reproductive capacity of men (Frapsauce et al ., ; Jerónimo et al ., ). It has been observed that antiretroviral therapy is associated with an increased amount of collagen deposits in the testes evidenced by interstitial fibrosis, cellular infiltration, and thickening of the basement membrane of the seminiferous tubules (Ogedengbe et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Semen parameters in HIV+ men attending fertility clinics have been extensively studied. Overall, relatively mild alterations were reported, along with modifications to the sperm mitochondrial DNA (324,691). These alterations, observed in asymptomatic men with controlled viral loads, are believed to occur as a secondary effect of antiretroviral molecules and not as a consequence of the infection itself.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 96%